Serum FAM19A5 in neuromyelitis optica spectrum disorders: Can it be a new biomarker representing clinical status?. (November 2020) - Lee, Hye Lim; Seok, Hung Youl; Ryu, Han-Wook; Cho, Eun Bee; Kim, Bong Chul; Kim, Byoung Joon; Min, Ju-Hong; Seok, Jin Myoung; Shin, Ha Young; Kang, Sa-Yoon; Kwon, Oh-Hyun; Lee, Sang-Soo; et al.
Background: Neuromyelitis optica spectrum disorder (NMOSD) targets astrocytes and elevates the levels of astrocyte-injury markers during attacks. FAM19A5, involved in reactive gliosis, is secreted by reactive astrocytes following central nervous system (CNS) damage. Objective: To investigate the significance of serum FAM19A5 in patients with NMOSD. Methods: We collected clinical data and sera of 199 patients from 11 hospitals over 21 months. FAM19A5 levels were compared among three groups: NMOSD with positive anti-aquaporin-4 antibody (NMOSD-AQP4), other CNS demyelinating disease, and healthy controls. Results: The median serum FAM19A5 level was higher in the NMOSD-AQP4 (4.90 ng/mL (3.95, 5.79)) than in the other CNS demyelinating (2.35 ng/mL (1.83, 4.07), p  < 0.001) or healthy control (1.02 ng/mL (0.92, 1.14), p  < 0.001) groups. There were significant differences in the median serum FAM19A5 levels between the attack and remission periods (5.89 ng/mL (5.18, 6.98); 4.40 ng/mL (2.72, 5.13), p  < 0.001) in the NMOSD-AQP4 group. Sampling during an attack ( p  < 0.001) and number of past attacks ( p  = 0.010) were independently associated with increased serum FAM19A5. Conclusion: Serum FAM19A5 was higher in patients with NMOSD-AQP4 and correlated with clinical characteristics. Thus, serum FAM19A5 may be a novel clinical biomarker for NMOSD-AQP4.